REMEDIATION OF EXPONENT NUMBERS MISCONCEPTIONS IN SEVENTH GRADE STUDENTS THROUGH A PROBLEM POSING APPROACH - Liora, Priscilla Josierra; Sugioatno, Sugioatno; Hamdani, Hamdani (Universitas Sembilanbelas November Kolaka, 2025)
This study aims to remediate students' misconceptions about exponent numbers using a problem posing approach among seventh-grade students at SMP Negeri 26 Pontianak. Misconceptions in mathematics are a fundamental issue that can hinder students’ understanding of more advanced concepts if not addressed effectively. The problem posing approach offers an innovative solution by encouraging active student participation, creative thinking, and deeper conceptual understanding. This research employed Pedagogic Action Research with a qualitative approach. The subjects were five seventh grade students who selected based on diagnostic test results that identified specific misconceptions related to the concept of exponents, such as powers of zero, negative exponents, and the order of operations. Data were collected through diagnostic tests, interviews, observations, and posttests. The misconceptions are concepts of exponent, powers of zero, exponent with negative numbers, and the order of counting operations. The results revealed that the post-solution posing type of problem posing approach effectively reduced students' misconceptions. After the remediation, misconceptions among the five subjects were reduced to only one, specifically regarding the concept of zero exponents. These results indicate that the problem posing approach can be a powerful strategy in helping students overcome persistent misconceptions in mathematics through active engagement and reflective learning.